DUALISME EKONOMI PADA KREDIT RAKYAT DI YOGYAKARTA PADA TAHUN 1912-1990 - Arif Akhyat (Humaniora, 2015)
The development of capitalism idea during the colonial prior to the New Order periods need a broader understanding of an historical analysis of popular credit case in Yogyakarta 1912-1990. The establishment of bank in Yogyakarta was already accomplished in the sense that it was owned and managed by state and it sell a large proportion of credit products on the open of financial system in villages. Using the historical critical method, this research seems to be the most appropriate for obtaining meaningful information on descriptions, dynamics, changes and tendencies of the  functional relationship between credit systems, state authority and the process of economic transformation in the region of Yogyakarta. Designing with the capitalism system, government credit system was not able to increase a village economy position in Yogyakarta. Popular Credit in the years of 1912-1990 as this research mentioned, is far from what villagers need. Banking system, in practices, was designed to create and produce a subsisten economy. The dual economy experiences of popular credit in Yogyakarta historically had given the state to be the hegemony holder. Popular credit is no more or less as the construct of economic boundaries under the concept of colonialism